Communication Management in Preventing Negative Impact of Online Games on Students in Elementary School - Kartikawati, Dwi; Nurhasanah, Nurhasanah (Green Publisher Indonesia, 2023)
The research focuses on how Communication Management in Preventing the Negative Impact of Online Games on Students at SD Negeri 09 South Jakarta. The phenomenon of using online games among elementary school children is very widespread, which is feared is the negative impact experienced by elementary school students. These impacts include students who are addicted to being lazy such as children not interacting with people around them, lazy to study or do assignments from school, negative performance, lazy school, lazy to eat, difficult to concentrate and only interested in playing games. These elementary school children have not been able to filter out what is right or wrong to apply in their lives. For this reason, it is necessary to manage school communication in order to develop good communication to prevent the negative impact of online games at SD Negeri 09 Jakarta. Because through good communication management carried out by school residents, students in this elementary school can take advantage of technology and become media literate so as to avoid negative behavior of online online games. By using the concept of communication management, and the concept of online games, and the concept of elementary school. The methodology used in this research is a qualitative method with in-depth interviews with principals, teachers, students and parents and conducting data validity tests with data credibility tests.